Risk management practice in China’s Public-Private Partnership projects - Ke, Yongjian; Wang, ShouQing; Chan, Albert P. C. (Journal of Civil Engineering and Management, 2012)
Project risks were not properly managed in the many past Public-Private Partnership (PPP) projects in China. Although numerous research studies have been conducted on risk management in China’s PPP projects, the realization of risk management in China’s construction industry especially in PPP projects with high risk exposure and complicated contract structure has hitherto not been well studied. This paper therefore attempted to examine the current use of risk management in China’s PPP projects by an empirical survey. The results indicated that the use of risk management was inadequate; qualitative risk analysis methods were preferred to quantitative and semi-quantitative methods; risk management usage in the execution was found to be much higher than in the planning, conceptual or termination stage; interviewees were unfamiliar with most of the risk identification and assessment tools. All above could be partly due to the project nature, but more fundamentally due to the local industrial culture. The absence of risk management culture was found to be the dominant factor which limited the implementation of risk management in practice. Recommendations to alleviate the difficulties of risk management were thereafter provided in this paper.